2017
DOI: 10.18203/2394-6040.ijcmph20170769
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life of stroke survivors in a rural area of North Kerala, India

Abstract: Background: With increase in prevalence of stroke and life expectancy the quality of life of stroke survivors assumes importance. Despite advances in diagnosis and treatment of cerebrovascular accidents the survivors continue to experience low Quality of life (QoL) especially in developing countries. The objective of this study was to assess the quality of life among stroke survivors and the prevalence of depression among them.  Methods: Cross-sectional population based study was conducted in a rural area of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This study showed that being a male was not found to be a significant factor of improved ADL. The result was consistent with a study in India which reported men were unable to regain independence in ADL after a stroke as much as women 44 due to the high prevalence of poststroke depression (PSD). They were expected to have reduced contact with others and lack motivation to improve after stroke.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that being a male was not found to be a significant factor of improved ADL. The result was consistent with a study in India which reported men were unable to regain independence in ADL after a stroke as much as women 44 due to the high prevalence of poststroke depression (PSD). They were expected to have reduced contact with others and lack motivation to improve after stroke.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was one of the major determinants of QoL, which was found to be poor. 25 In a study done by Jonsson found that the patients' most important determinants of QOL after 16 months were functional status, age and gender. 8 The strength of our study is the low dropout rate in the form of loss to follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Poor SF-36 score in all domains with specifically lowest scores in the domains of "role limitations due to physical problems and "physical function" was also reported for stroke patients living in Kerala state of Southern India [16].…”
Section: Quality Of Lifementioning
confidence: 73%